2004
DOI: 10.1143/jjap.43.4972
|View full text |Cite
|
Sign up to set email alerts
|

Write-Once Disk with BiFeO Thin Films for Multilevel Optical Recording

Abstract: The surface free energies, interfacial tensions and correlation lengths of the Andrews-Baxter-Forrester models in regimes III and IV are calculated with fixed boundary conditions. The interfacial tensions are calculated between arbitrary phases and are shown to be additive. The associated critical exponents are given by 2 − α s = µ = ν with ν = (L + 1)/4 in regime III and 4 − 2α s = µ = ν with ν = (L + 1)/2 in regime IV. Our results are obtained using general commuting transfer matrix and inversion relation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For write-once HD-DVDs and BDs, the recording materials can be either organic dyes 1,2) or inorganic metallic alloys. 3) Phase-change-based alloys, 4) single-layer AlSi alloys, 5,6) bilayer metals such as Cu/Si 7) and Zn/Ge, 8) and metallic nitrides 9) have been reported for write-once disk applications. However, regardless of the recording material types, complicated 4 to 8 multilayer structures consisting of lower and upper dielectric layers, a recording layer, a space layer, and a reflection layer are usually required for the optical disks to ensure a reliable lifetime for data storage.…”
Section: Introductionmentioning
confidence: 99%
“…For write-once HD-DVDs and BDs, the recording materials can be either organic dyes 1,2) or inorganic metallic alloys. 3) Phase-change-based alloys, 4) single-layer AlSi alloys, 5,6) bilayer metals such as Cu/Si 7) and Zn/Ge, 8) and metallic nitrides 9) have been reported for write-once disk applications. However, regardless of the recording material types, complicated 4 to 8 multilayer structures consisting of lower and upper dielectric layers, a recording layer, a space layer, and a reflection layer are usually required for the optical disks to ensure a reliable lifetime for data storage.…”
Section: Introductionmentioning
confidence: 99%
“…6 Inorganic-type materials include phase-change alloys, 7 single-layer AlSi alloys, 8 bilayer metals such as Cu/ Si, 9 Zn/ Ge, 10 Ge/ Au, 11 Cu/ a-Si, 12 etc. Among these, Bi-related alloys such as Bi-Ge alloy 13,14 and Bi oxide ͑BiFeO͒ 15,16 exhibit promising applications for write-once data storage. For Bi-Ge-͑N͒ alloy, the recording mechanism was attributed to the reflectivity change caused by the decomposition of Bi nitride in the recording layer as well as the deformation in recording marks due to the gas release.…”
mentioning
confidence: 99%
“…At present, recording materials compatible with blue-laser recording are of particular interest. For such materials, organic ones are dyes that are sensitive to blue irradiation while inorganic ones include phase-change-based alloys, 5,6) AgInSbTe-SiO 2 nanocomposite films, 7,8) single layer metals such as AlSi alloys, 9,10) bismuth oxide (BiFeO) [11][12][13] and Bi-Fe-(N) layer, 14) and bilayer metals such as Ge/Au, [15][16][17][18] Cu/Si, 19) ZnO/Ge, 20) amorphous silicon (a-Si)/Cu, [21][22][23][24] a-Si/Al, 24,25) a-Si/Ni, [26][27][28] and Bi/Ge. 29,30) In our previous study, 14) the Bi-Fe-(N) system was demonstrated to be a promising medium for high-density write-once recording.…”
Section: Introductionmentioning
confidence: 99%